Retrospective investigation of postoperative mid-term results of cryoablation and radiofrequency ablation methods used in atrial fibrillation surgery treatment - Tatlı, Ahmet Burak; Pala, Arda Aybars; Engin, Mesut; Taner, Temmuz; Ata, Yusuf (The European Research Journal, 2021)
Objectives: Atrial fibrillation (AF) is the most common arrhythmia encountered and is usually seen in patients scheduled for coronary artery bypass and mitral valve surgery. Radiofrequency ablation and cryoablation are two methods used in AF surgery and proven efficacy. In this study, cryoablation and radiofrequency ablation methods were compared in terms of clinical outcomes, efficacy and safety. Methods: Between November 2011 and September 2017; 99 patients with AF who underwent radiofrequency ablation or cryoablation during open heart surgery were included in this study with 2 groups. The patients who underwent cryoablation were defined as Group I (n = 40), and the patients who underwent radiofrequency ablation as Group II (n = 59). Preoperative, perioperative, early and mid (1 year) postoperative period characteristics of the groups were analyzed. Results: The mean age was 60.6 ± 9 years in Group I and 60.7 ± 9.1 years in Group II (p = 0.960). When the operative values were examined, ablation time and cross-clamp time was found to be low in Group II and a statistically significant difference was found (p < 0.001 and p = 0.043; respectively). When the rhythms of the postoperative first year controls are examined, sinus rhythm was observed in 34 (85%) patients in Group I and 50 (84.7%) patients in Group II. There was no statistically significant difference in return to sinus rhythm in the first year (p = 0.975). Conclusions: The success rates of these two methods used in AF surgery are effective but they are not superior to each other.